Development of CdZn(SSe)2 thin films by using simple aqueous chemical route: Air annealing. (2017) - Jagadale, S.K.; Shinde, D.B.; Mane, R.M.; Ghanwat, V.B.; Khot, K.V.; Mane, R.K.; Bhosale, P.N.
Abstract: In the present investigation we have successfully depositedCdZn(SSe)2 thin films by using facile self organised Arrested Precipitation Technique (APT).Preparative conditions were optimized during initial stage of experimentation to obtain good quality CdZn(SSe)2 thin film.The resulted thin film was annealed in air at 373K for 1hr. FurtherOptical, structural, morphological and compositional properties of annealed thin filmswere investigated.The optical band gap value of thin film was estimated from the absorption spectrum which is found to be 1.85 eV. X-ray diffraction (XRD) study reveals that grown CdZn(SSe)2 thin film was nanocrystalline with hexagonalcrystal structure.The SEM micrograph shows the formation of layered structure containing dense layer covered by uniform distribution of spherical grains. Energy dispersive X-ray (EDS) analysis confirm the presence of Cd, Zn, S and Se elements in the synthesized and annealed thin film. The film was obtained with a well-defined composition, very close to the expected atomic percentage.